Bibliometric Analysis Of Dynamic Capability Research In The Last Decade - Santi Marlina Hutahaean; Roy Valiant Salomo (Eduvest - Journal of Universal Studies, 2025)
Over the past decade, the concept of dynamic capabilities has gained increasing attention in public policy and administration studies. This concept highlights the importance of the ability of governments and organizations to adapt quickly, engage in continuous learning, and promote innovation in the face of complex and dynamic environmental changes. This study aims to understand the direction and development of research related to dynamic capabilities through a bibliometric approach. An analysis was conducted on 336 scientific articles indexed in the Scopus database from 2014 to 2024. The data was then processed and visualized using the VOSviewer application to identify publication trends, influential journals, main contributing authors and countries, as well as emerging research themes. The results of this study reveal three main findings. First, there has been a significant increase in the number of publications from 2021 to 2024, indicating growing scientific interest in this topic. Second, Journal Long Range Planning is the most influential journal in terms of citations, publications, and influential articles. Third, the largest contributions come from academics in the United States, the United Kingdom, and China. Fourth, a number of topics were found to be under-explored, such as leadership, learning, absorptive capacity, organizational change, and innovation performance, which have great potential for future development. This study makes an important contribution to mapping the scientific landscape of dynamic capabilities and can serve as a strategic reference for academics, practitioners, and policymakers in strengthening the resilience and transformation of public organizations.